Expanding Single, Double and Triple Brackets

Easy

Medium

Difficult

Q1) 3(y + 1) =
Q1) \((w + 2)(w + 1)\)
Q1) \((x + 4)(x + 1)(x -3)\)
Q2) 2(w + 4) =
Q2) \((z + 4)(z + 2)\)
Q2) \((x + 3)(x + 3)(x -5)\)
Q3) 5(2x + 9) -10x + 7 =
Q3) \((4x + 3)(3x -2)\)
Q3) \((x + 4)(x + 3)(x + 4)\)
Q4) 4(x + 3) =
Q4) \((9x + 1)(6x -2)\)
Q4) \((x + 6)(x + 3)(x + 2)\)
Q5) 4(z + 3) =
Q5) \((z + 5)(z + 3)\)
Q5) \((x + 1)(x + 4)(x + 4)\)
Q6) 5(2z -9) -5z -10 =
Q6) \((6x + 3)(8x -2)\)
Q6) \((x + 4)(x + 5)(x -4)\)
Q7) 2(2y -9) +2y -7 =
Q7) \((2x + 2)(4x -2)\)
Q7) \((x + 1)(x + 5)(x + 3)\)